An agent-based approach to modeling zero energy communities. (October 2019) - Mittal, Anuj; Krejci, Caroline C.; Dorneich, Michael C.; Fickes, David
Highlights: This paper describes a community level approach to achieve zero energy objectives. An agent-based model is developed to study renewable energy adoption by consumers. Multiple renewable energy options are modeled simultaneously to study adoption. The results highlight the importance of community solar to increase adoption. Social interactions among consumers significantly affect their adoption decisions. Abstract: As zero energy buildings take on an increasingly prominent role in overall efforts to reduce energy consumption, it is necessary to identify effective policies for their design and implementation. However, current zero energy building (ZEB) policies focus mainly on new buildings, primarily through on-site renewable energy generation, such as rooftop photovoltaic (PV) systems. Having a few high performing buildings will have limited impact if the community as a whole is not net zero. A more practical approach to achieve zero energy goals is to extend the zero energy boundaries beyond an individual building and have a group of buildings evaluated together as a community, such that the community in itself becomes a zero-energy community (ZEC). Successful ZEC implementation requires that community members actively participate in renewable energy and energy efficiency programs and collectively support the goal of zero energy. Hence, a consumer-oriented analysis is needed to support effective ZEC design decisions and promotion efforts. This paper describes a conceptual agent-based model for an urban neighborhood in Des Moines, Iowa, to predict household level renewable energy adoption behaviors in presence of multiple options. Specifically, the level of consumer participation before and after introducing a community solar option for the neighborhood is evaluated via experimentation with the model. Simulation results demonstrate that introducing a community solar program increases household level adoption as well as the proportion of community level electricity consumption met through renewable sources. The amount of increase in adoption, however, depends on the choice of design parameters, such as premium that households must pay to participate. The results also show that timeliness of achieving ZEC goals depends upon the frequency of social interactions in the neighborhood, indicating the importance of community events in the successful creation of a ZEC.